2020
DOI: 10.1111/mmi.14529
|View full text |Cite
|
Sign up to set email alerts
|

Interaction with single‐stranded DNA‐binding protein localizes ribonuclease HI to DNA replication forks and facilitates R‐loop removal

Abstract: Replisomes are protein complexes that catalyze high-fidelity DNA replication at speeds approaching 1,000 bp/sec in bacteria (Chandler et al., 1975; O'Donnell et al., 2013). During the replication process replisomes encounter numerous impediments to their progress including protein/DNA complexes, non-duplex nucleic acid structures, and chromosomal damage (Mirkin and Mirkin, 2007). To overcome these obstacles, cells have evolved several systems that support replication on imperfect genomic templates. These inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 112 publications
(159 reference statements)
0
23
0
Order By: Relevance
“…3 G and 5 A ), raising the possibility of yet undiscovered roles for SSB in RNA metabolism. Indeed, recently SSB was found to enhance the function of RNase HI in R-loop removal ( 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…3 G and 5 A ), raising the possibility of yet undiscovered roles for SSB in RNA metabolism. Indeed, recently SSB was found to enhance the function of RNase HI in R-loop removal ( 56 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since the chromosomally-located reporters gyrB::lacZ and topA::lacZ , showed wild-type levels of topoisomerase activity in Δ rnhC p rnhC , but only report on the topology status of the chromosome, we concluded that the increased number of R-loops detected in the complemented ΔrnhC strain must therefore be plasmid-borne. It is possible that increased hyper-negative supercoiling of the plasmid, either through localised transcription effects (48) and/or titration of RNase HI activity to the chromosome (49), may have affected binding efficiencies of some of the proteins involved in plasmid replication, resulting in increased initiation frequencies, as well as promotion of R-loop formation.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Arabidopsis OSB1 was reported to function together with ribonuclease (RNase) H1 in decreasing the formation of R‐loops in mitochondria (Cheng et al, 2021). In E. coli , the interaction of SSB and RNase HI localizes RNase HI to DNA replication sites and facilitates the removal of R‐loops that block DNA replication (Wolak et al, 2020). Considering that OSB1 is also an ssDNA‐binding protein, we propose that SSB1, alone or with SSB2, competes with OSB1 to bind to ssDNA at R‐loop sites to balance mtDNA replication and mtDNA HR surveillance (Figure S4).…”
Section: Discussionmentioning
confidence: 99%